The relationship between alexitymia and emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof; Mansor, Mariani (Canadian Center of Science and Education, 2010)
The article reviews empirical studies which emphasized on the relation between alexitymia and emotional intelligence (EQ). EQ is a set of abilities such as conception, emotion appraisal and expression, emotion management and regulation, and emotion utilization of emotion. As emotional intelligence is acquisitive and of social origin, parents and children thus expose their emotions in an expressive way to one another, either consciously or unconsciously in their interactions. Adolescence’s alexithymia overlay emotional intelligence in the field of emotion identification and to some extent, in feelings expression. Alexithymic adolescence cannot express emotions orally due to inability in feelings identification, whereas preliminary emotional abilities have specific importance because skillfulness in appraisal and quick precise expression of emotions brings about suitable compatibility in relation with environment and others. The research showed that emotional intelligence is negatively associated with alexithymia. The article is divided into several sections. The review is started with the definition of alexithymia, and this is followed by a review on the alexithymia, as well as the effects and interaction of emotional intelligence. Then, an overview of the paper is included a demonstration of the influence of alexithymia on emotional intelligence is also given. Finally, according to previous study it is important to realize that alexithymia does not imply a total unawareness of having emotions.